A method for preparing a lithium battery negative electrode material based on benzothiadiazole covalent organic framework
By adopting a negative electrode material preparation method based on a benzothiadiazolyl covalent organic frame in lithium-ion batteries, the problems of volume expansion and limited active sites of traditional materials after circulation are solved, and high specific capacity and stable cycling performance are achieved.
Patent Information
- Application Number
- CN202411156820.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-08-21
AI Technical Summary
The existing lithium-ion battery negative electrode materials have volume expansion problems after multiple cycles, and the active sites of traditional two-dimensional COFs are limited and have poor crystallinity, making it difficult to accumulate into block materials through π-π interaction, resulting in a lower actual specific capacity.
Using a lithium battery negative electrode material preparation method based on a benzothiadiazole-based covalent organic frame, the COF at multiple redox active sites is synthesized and mixed with conductive carbon black and adhesive to form a uniform negative electrode slurry, and the negative electrode sheet is obtained by casting and vacuum drying.
It improves structural stability and conductivity, provides more lithium storage sites, enhances π-π interaction, forms a solid and stable framework structure, allowing lithium ions to diffuse quickly, achieving high discharge capacity and stable cycling performance.
Smart Images

Figure CN118983441B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium battery electrode materials, and in particular relates to a method for preparing a lithium battery negative electrode material based on a benzothiadiazole-based covalent organic framework. Background Art
[0002] The application of lithium-ion batteries has expanded from portable electronic devices to large equipment and electric vehicles. The next generation of lithium-ion batteries will continue to develop towards higher energy density, which mainly depends on the properties of electrode materials. In recent years, the negative electrode active materials of lithium-ion batteries are mainly inorganic compounds based on silicon, phosphorus, silicon carbon and lithium carbon. Silicon-based and phosphorus-based materials have high theoretical specific capacities. However, silicon-based electrodes will face severe volume expansion after multiple cycles, while phosphorus-based electrodes have poor conductivity. Covalent organic frameworks (COFs) have become promising organic electrode materials due to their ordered crystal structure and porosity. COFs have abundant redox active sites, tunable pores and framework structures, low electrolyte solubility and environmental friendliness. Among them, COFs containing carbonyl (C=O), imine functional groups (C=N, N=N), free radicals, benzene rings and other functional groups have been studied and used for the storage of negative lithium ions.
[0003] Studies have shown (Adv. Sci. 2022, 9, 2105213) that rich and diverse redox active sites are the key to achieving high theoretical specific capacity. However, the actual capacity is affected by many factors, including the interlayer structure, particle size, electronic conductivity and pore size of COF. Zhao et al. (Adv. Funct. Mater. 2021, 31, 2101019) synthesized E-TP-COF with dual active sites for positive electrode lithium storage, but its actual specific capacity is low, only 110 mAh g -1 Therefore, designing and synthesizing COF-based anodes with high cycle stability and rate performance remains a challenge, and traditional two-dimensional COFs have limited active sites and poor crystallinity, making it difficult to stack into bulk materials through π-π interactions. Summary of the invention
[0004] In view of the above problems, the present invention proposes a method for preparing a negative electrode material for a lithium battery based on a benzothiadiazolyl covalent organic framework, synthesizes a COF with multiple redox active sites (C=O and C=N) and successfully uses it for negative electrode lithium storage. The presence of the C=O unit enhances the π-π interaction, thereby improving the structural stability and conductivity; it has a rich pore structure, can provide more lithium storage sites, and improve the specific capacity. This pore structure can also solve the problem of volume expansion to a certain extent.
[0005] The technical solution adopted by the present invention to solve the above problems is as follows:
[0006] A method for preparing a lithium battery negative electrode material based on a benzothiadiazole-based covalent organic framework comprises the following steps:
[0007] S1. Add monomer 1 and 4,7-bis(4-aminophenyl)-2,1,3-benzothiadiazole to a reaction tube, then add a reaction solvent to obtain a mixture, disperse the mixture evenly by ultrasonic wave, and then completely degas the mixture by three freeze-pump-thaw cycles, seal and heat the degassed reaction tube, filter and separate the solid after the reaction is completed and cooled to room temperature, wash with a solvent, and then dry to obtain a covalent organic framework material;
[0008] S2, stirring and mixing the covalent organic framework material obtained in step S1, conductive carbon black and a binder in N-methylpyrrolidone until a uniform negative electrode slurry is obtained;
[0009] S3, pouring the negative electrode slurry obtained in step S2 on the copper current collector and scraping it to a certain thickness, then drying it in a vacuum drying oven, and cutting it into discs to obtain a lithium battery negative electrode sheet based on the covalent organic framework.
[0010] In the preparation method as described above, the monomer 1 in step S1 is trimesaldehyde, 2-hydroxy-1,3,5-benzenetricarbaldehyde, 2,4-dihydroxy-1,3,5-benzenetricarbaldehyde or trialdehyde phloroglucinol.
[0011] In the preparation method as described above, the molar ratio of monomer 1 to 4,7-bis(4-aminophenyl)-2,1,3-benzothiadiazole in step S1 is (1-3):(2-4).
[0012] In the preparation method as described above, the reaction solvent in step S1 is one or more of trimethylbenzene, m-xylene, 1,4-dioxane, pyrrolidine, n-butanol and acetic acid.
[0013] In the preparation method as described above, in step S1, the ultrasonic treatment time is 30 to 60 minutes, preferably 30 minutes.
[0014] In the above-mentioned method for preparing a lithium battery negative electrode material based on a benzothiadiazole-based covalent organic framework, in step S1, the heating temperature of the reaction tube is 120° C. and the heating time is 72 hours.
[0015] In the preparation method as described above, the washing solvent in step S1 is methanol, tetrahydrofuran and acetone, and the number of times is 3 to 6 times, preferably 3 times.
[0016] In the preparation method as described above, in step S2, the mass ratio of the covalent organic framework material, the conductive carbon black and the binder is 6:3:1.
[0017] In the preparation method as described above, in step S3, the coating thickness is 100-400 μm, preferably 400 μm.
[0018] In the preparation method as described above, the vacuum drying conditions in step S4 are as follows: the drying temperature is 40-80° C., preferably 60° C., and the drying time is 6-12 h, preferably 12 h.
[0019] The present invention has the following beneficial effects:
[0020] The present invention provides a method for preparing a lithium battery negative electrode material based on a benzothiadiazolyl covalent organic framework. The synthesized COF material has a rich pore structure, multiple redox active centers, and strong interlayer π-π interactions, which provides more lithium storage sites while forming a strong and stable framework structure, allowing lithium ions to diffuse rapidly in the framework pores, and exhibits high discharge capacity and stable cycle performance when used as a lithium battery negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is the preparation process of the benzothiadiazole-based covalent organic framework material obtained in Examples 1 to 3 of the present invention and Comparative Example 1.
[0022] Figure 2 This is a scanning electron microscope (SEM) image of the benzothiadiazolyl covalent organic framework material COF-3 obtained in Example 3 of the present invention.
[0023] Figure 3 It is the polycrystalline X-ray diffraction pattern (PXRD) of the benzothiadiazolyl covalent organic framework material obtained in Examples 1 to 3 of the present invention and Comparative Example 1.
[0024] Figure 4 It is a nitrogen adsorption isotherm diagram and pore size distribution diagram of the benzothiadiazolyl covalent organic framework negative electrode material obtained in Example 3 of the present invention.
[0025] Figure 5 It is a rate performance diagram of the benzothiadiazolyl-based covalent organic framework negative electrode material obtained in Examples 1 to 3 of the present invention and Comparative Example 1.
[0026] Figure 6 This is a cycle performance diagram of the benzothiadiazolyl-based covalent organic framework negative electrode material obtained in Example 3 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0027] The specific implementation modes of the present invention are described in detail below with reference to the accompanying drawings.
[0028] The experimental methods described in the examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0029] Example 1
[0030] S1. Add 2-hydroxy-1,3,5-benzenetricarboxaldehyde (0.2mmol) and 4,7-bis(4-aminophenyl)-2,1,3-benzothiadiazole (0.3mmol) to the reaction tube, followed by m-xylene (1.5mL), 1,4-dioxane (1.5mL) and acetic acid (0.3mL). Ultrasonicate the suspension for 30min to ensure that the mixed solution is evenly dispersed. Degassing is completed by three freeze-pump-thaw cycles. Subsequently, seal the reaction tube and heat at 120°C for 72h. After cooling, filter and separate the solid, and wash it three times with excess methanol, tetrahydrofuran and acetone in sequence. After drying, a brown-red covalent organic framework material, namely COF-1, is obtained;
[0031] S2, stirring and mixing the covalent organic framework COF-1, conductive carbon black and adhesive obtained in step S1 in a mass ratio of 6:3:1 in N-methylpyrrolidone until a uniform negative electrode slurry is obtained;
[0032] S3. Pour the negative electrode slurry obtained in step S2 onto the copper current collector and scrape it to 400 μm, then dry it in a vacuum drying oven at 60° C. for 12 h, and cut it into discs to obtain a lithium battery negative electrode sheet based on the covalent organic framework COF-1.
[0033] Example 2
[0034] S1. Add 2,4-dihydroxy-1,3,5-benzenetricarboxaldehyde (0.2mmol) and 4,7-bis(4-aminophenyl)-2,1,3-benzothiadiazole (0.3mmol) to the reaction tube, followed by m-xylene (1.5mL), 1,4-dioxane (1.5mL) and acetic acid (0.3mL). Then ultrasonicate the suspension for 30min to ensure that the mixed solution is evenly dispersed. Degassing is completed by three freeze-pump-thaw cycles. Subsequently, seal the reaction tube and heat at 120°C for 72h. After cooling, filter and separate the solid, and wash it three times with excess methanol, tetrahydrofuran and acetone in sequence. After drying, a brownish-yellow covalent organic framework material, namely COF-2, is obtained;
[0035] S2, stirring and mixing the covalent organic framework COF-2, conductive carbon black and binder obtained in step S1 in a mass ratio of 6:3:1 in N-methylpyrrolidone until a uniform negative electrode slurry is obtained;
[0036] S3. Pour the negative electrode slurry obtained in step S2 onto the copper current collector and scrape it to 400 μm, then dry it in a vacuum drying oven at 60° C. for 12 h, and cut it into discs to obtain a lithium battery negative electrode sheet based on the covalent organic framework COF-2.
[0037] Example 3
[0038] S1. Add trialdehyde pyrogallol (0.2mmol) and 4,7-bis(4-aminophenyl)-2,1,3-benzothiadiazole (0.3mmol) into the reaction tube, followed by trimethylol (1.5mL), 1,4-dioxane (1.5mL) and pyrrolidine (0.3mL). Ultrasonicate the suspension for 30min, and then degas through three freeze-pump-thaw cycles. Heat the degassed reaction tube at 120°C for 72h. After cooling to room temperature, filter and separate the solid, and wash it three times with excess methanol, tetrahydrofuran and acetone in turn. After drying, a red covalent organic framework material, namely COF-3, is obtained;
[0039] S2, stirring and mixing the covalent organic framework COF-3, conductive carbon black and adhesive obtained in step S1 in a mass ratio of 6:3:1 in N-methylpyrrolidone until a uniform negative electrode slurry is obtained;
[0040] S3. Pour the negative electrode slurry obtained in step S2 onto the copper current collector and scrape it to 400 μm, then dry it in a vacuum drying oven at 60° C. for 12 h, and cut it into discs to obtain a lithium battery negative electrode sheet based on the covalent organic framework COF-3.
[0041] Comparative Example 1
[0042] Compared with Example 3, the main difference is that the trialdehyde phloroglucinol is replaced by hydroxyl-free pyromellitic aldehyde;
[0043] S1. Add trimesaldehyde (0.2mmol) and 4,7-bis(4-aminophenyl)-2,1,3-benzothiadiazole (0.3mmol) into the reaction tube, followed by n-butanol (1.5mL) and acetic acid (0.3mL). Ultrasonicate the suspension for 30min, and then degas through three freeze-pump-thaw cycles. Heat the degassed reaction tube at 120°C for 72h. After cooling to room temperature, filter and separate the solid, and wash it three times with excess methanol, tetrahydrofuran and acetone in turn. After drying, a brownish-yellow covalent organic framework material, namely COF-0, is obtained;
[0044] S2, stirring and mixing the obtained covalent organic framework COF-0, conductive carbon black and binder in N-methylpyrrolidone at a mass ratio of 6:3:1 until a uniform negative electrode slurry is obtained;
[0045] S3. Pour the negative electrode slurry obtained in step 2 onto the copper current collector and scrape it to 400 μm, then dry it in a vacuum drying oven at 60° C. for 12 h, and cut it into discs to obtain a negative electrode sheet based on the covalent organic framework COF-0.
[0046] Figure 1 This is the preparation process of Examples 1-3 of the present invention and Comparative Example 1. It can be seen that the number of carboxyl groups in COF-0~COF-3 gradually increases. These increased C=O can provide more storage sites for lithium ions and improve its specific capacity.
[0047] Figure 2 The stacked nanofiber structure of COF-3 is demonstrated, which makes it possible to provide a larger specific surface area.
[0048] Figure 3 The X-ray diffraction patterns of Examples 1 to 3 of the present invention and Comparative Example 1 show a prominent peak at 2.71°, which is more obvious in COF-3, indicating that it has high crystallinity. The sharpness and intensity of the (100) plane peak of COF-3 are improved, that is, the presence of the C=O unit partially enhances the π-π interaction, thereby improving the structural stability and conductivity.
[0049] Figure 4 The N2 adsorption isotherm and pore size distribution of COF-3 (inset) show a typical IV type adsorption isotherm with H3 or H4 hysteresis, proving its mesoporous characteristics (about 2.8 nm) and its specific surface area is as high as 1887.5 m 2 g -1 , which is conducive to the shuttling of lithium ions in the pores and can effectively inhibit the growth of lithium dendrites and the volume change of the electrode.
[0050] Figure 5 The figure is the rate performance diagram of Examples 1-3 of the present invention and Comparative Example 1. At lower current density, the specific capacity difference of different COFs is small, and the rate performance is similar. As the current density increases, the capacity advantage of the polycarbonyl COF-3 electrode becomes more obvious, showing the best overall performance. -1 When , the reversible capacities of COF-3 are 148, 119, 95 and 74 mAh g -1 . The current density was reduced to 0.1A g -1 When COF-3 electrode recovers 132 mAh g -1 , which indicates excellent structural stability even under high current conditions.
[0051] Figure 6 The cycle performance of Example 3 of the present invention and Comparative Example 1 is compared. At a low current density (0.2A g -1 ), the discharge capacity of the fully activated COF-3 electrode increased significantly to 217 mAh g -1 (500 cycles), which is much higher than the result of COF-0 electrode.
[0052] The highly crystalline stable framework and mesoporous structure provide a short and ordered transmission path for lithium ions, which, together with the intrinsic multiple lithium storage active centers of COF-3, is conducive to improving the rate performance; in addition, the strong π-π interaction between the two-dimensional COF layers inhibits the dissolution of COF in the electrolyte and improves its conductivity, which helps to maintain a stable cycle.
[0053] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
[0054] Although the above describes the specific implementation methods of the present invention, it is not intended to limit the scope of protection of the present invention. Those skilled in the art should understand that various modifications or variations that can be made by those skilled in the art on the basis of the technical solution of the present invention without creative work are still within the scope of protection of the present invention.
Claims
1. A method for preparing a negative electrode sheet for a lithium battery based on a benzothiadiazole covalent organic framework, characterized in that: The preparation method comprises the following steps: S1. Add monomer (1) and 4,7-bis(4-aminophenyl)-2,1,3-benzothiadiazole to a reaction tube, then add a reaction solvent to obtain a mixture, disperse the mixture evenly by ultrasonic wave, and then completely degas the mixture by three freeze-pump-thaw cycles, seal and heat the degassed reaction tube, filter and separate the solid after the reaction is completed and cooled to room temperature, wash with a solvent, and then dry to obtain a covalent organic framework material; the heating temperature of the reaction tube is 120° C., and the heating time is 72 h; S2, stirring and mixing the covalent organic framework material, conductive carbon black and adhesive obtained in step S1 in N-methylpyrrolidone until a uniform negative electrode slurry is obtained; S3, pouring the negative electrode slurry obtained in step S2 on the copper current collector and scraping it to a certain thickness, then drying it in a vacuum drying oven, and cutting it into discs to obtain a negative electrode sheet of a lithium battery based on a covalent organic framework; In step S1, the molar ratio of the monomer (1) to 4,7-bis(4-aminophenyl)-2,1,3-benzothiadiazole is 1-3:2-4; The monomer (1) in step S1 is trialdehyde phloroglucinol.
2. The preparation method according to claim 1, characterized in that: The reaction solvent in step S1 is one or more of trimethylbenzene, m-xylene, 1,4-dioxane, pyrrolidine, n-butanol and acetic acid.
3. The preparation method according to claim 1, characterized in that: The ultrasonic treatment time is 30~60min.
4. The preparation method according to claim 1, characterized in that: The washing solvents are methanol, tetrahydrofuran and acetone, and the washing times are 3 to 6 times.
5. The preparation method according to claim 1, characterized in that: In the step S2, the mass ratio of the covalent organic framework material, the conductive carbon black and the binder is 6:3:
1.
6. The preparation method according to claim 1, characterized in that: The coating thickness in step S3 is 100-400 μm.
7. Application of the benzothiadiazolyl covalent organic framework lithium battery negative electrode sheet prepared by the preparation method according to any one of claims 1 to 6 in lithium batteries.
Citation Information
Patent Citations
Covalent organic framework material / carbon nanotube organic composite material and application thereof in lithium ion battery
CN113903899A